2011
DOI: 10.1111/j.1747-6593.2010.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of trichloroethylene in groundwater of the industrial complex in Wonju, Korea: a 15‐year dispute and perspective

Abstract: The groundwater of an industrial complex has been contaminated with trichloroethylene (TCE) since 1995. High levels of TCE exceeding the Korean groundwater standard can still be found. However, ongoing controversial debate on the contamination source has hindered the remedial works. Wonju city suggested a single source, while the Gangwon Province considered multiple sources. The TCE plume appeared as two separate plumes rather than a single plume. Carbon tetrachloride (CT), a formerly used solvent, formed a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
2

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 12 publications
0
52
0
2
Order By: Relevance
“…The most important issue is about the apportionment of the TCE contamination. Apart from the Asphalt Test Institute, there are also other plausible sources of contamination of the groundwater such as a molding company, even though they are not expected to contribute to the contamination to a great extent (Baek and Lee, 2011;. Although it is practically obvious that the Asphalt Test Institute is the main source of the TCE contaminated groundwater at this site, the GRMO has not admitted responsibility for the contamination and has continuously suspended the remediation work of the contaminated groundwater.…”
Section: Groundwater Contaminationmentioning
confidence: 97%
See 4 more Smart Citations
“…The most important issue is about the apportionment of the TCE contamination. Apart from the Asphalt Test Institute, there are also other plausible sources of contamination of the groundwater such as a molding company, even though they are not expected to contribute to the contamination to a great extent (Baek and Lee, 2011;. Although it is practically obvious that the Asphalt Test Institute is the main source of the TCE contaminated groundwater at this site, the GRMO has not admitted responsibility for the contamination and has continuously suspended the remediation work of the contaminated groundwater.…”
Section: Groundwater Contaminationmentioning
confidence: 97%
“…It has been shown that groundwater in some urban areas is severely contaminated with various organic compounds (Park et al, 2005;Lee et al, 2010;Baek and Lee, 2011).…”
Section: Groundwater Monitoringmentioning
confidence: 99%
See 3 more Smart Citations